Advances in lead-free pyroelectric materials: a comprehensive review. Issue 5 (28th November 2019) - He, Hongying; Lu, Xin; Hanc, Emil; Chen, Chao; Zhang, Hao; Lu, Li
Abstract : Pyroelectric materials are important functional materials that can generate an electrical response upon a temperature change. In recent years, significant advances have been achieved in different types of lead-free pyroelectrics and are rising to potential energy-related applications. Abstract : Pyroelectric materials are important functional materials that can generate an electrical response upon a temperature change. Among the many different types of pyroelectric materials, lead-based materials are the most widely-used traditional pyroelectric material and they will soon be banned due to their high toxicity. Therefore, in the past decade, extensive studies have been conducted to search for high performance lead-free pyroelectric materials. Recent experimental efforts have led to significant advances in lead-free pyroelectrics in different forms. This has further motivated their application from a traditional sensing function to a future energy-related prospect. This article provides a comprehensive review on the up-to-date advances in lead-free pyroelectrics, including single crystals, ceramics, inorganic films, polymers and composites. Moreover, the recent rise in energy harvesting and the electrocaloric effect as well as the potential future development of pyroelectric applications will be presented.